Circadian clock: Time for novel anticancer strategies?. (October 2015) - Ercolani, Luisa; Ferrari, Alessio; Mei, Claudia De; Parodi, Chiara; Wade, Mark; Grimaldi, Benedetto
Graphical abstract: Abstract: Disruption of the circadian clock is associated with a variety of human pathologies, including cancer. Rather than being a mere consequence of a global changes associated with the cancer cell transcriptome, the aberrant clock gene expression observed in many tumors may serve for cancer cell survival. This scenario suggests the provocative hypothesis that pharmacological modulation of clock-related proteins may be suitable as an effective anticancer strategy. In this review, we focus on the functions of the druggable circadian nuclear receptors, REV-ERBα and REV-ERBβ, in cancer cell survival and describe the potential development of small molecule compounds that modulate REV-ERB activity as novel anticancer therapeutics. In addition, we debate the use of circadian rhythm-based synthetic lethal approaches to identify yet unexplored anticancer strategies.